A Critical Study on Missile and Missile Guidance: Exploring the Types and Classification of Missiles and Their Guidance Systems (Journal of Advances and Scholarly Researches in Allied Education, 2017)
With the increase in the technology of weapon system, there is great revolution in the concept of warfare. Technology as a force multiplier provides cutting edge and competitive in modern warfare. Modern warfare requires autonomous weapons. In the new era, missiles are known as the strength for a country. For a modern military inventory, guided weapons technology is a prerequisite. From very short range to short, medium and long range weapons and automated weapons are the topic for research. In this paper, a critical study is carried on different types of missiles and their classification based on their features like target, range, mode for launching and their autopilot guidance system.